Initial results of two module online courses III of the Construction + Extension Project (International Journal of Geoscience, Engineering and Technology, 2020)
The objective of this work was to promote the training of professionals and students in the field of civil construction and the like by offering online courses. The courses offered were “Real Estate Financing and Project Approval in City Halls” and “Mapping and Management of Risk Areas: Floods, Inundation and Slides on Slopes”, whose themes were chosen according to their relevance to complement the training of the target audience. The courses were offered in two different periods and were available for 7 days. The courses were published on the social networks Facebook, Instagram, Telegram, among others. In order for the course participants to obtain the certificate of completion of the course, it was necessary to meet three requirements: 1) Attend 100% of the classes; 2) Present at least 70% in the technical exam; and 3) Complete the satisfaction form. With the results obtained, it can be said that Module III of the Construction +Project reached a large number of course participants, since both courses had more than 700 and 400 registered, for the first and second periods, respectively. In general, about 35% of those registered met the prerequisites mentioned for obtaining the certificate. In relation to the satisfaction survey, about 50% of the students considered the professional contribution of the courses from medium to high.